Creativity of Regions and its Monitoring in Region of Žilina - Miriam Mocková; Petra Kunertova (European Regional Science Association (ERSA), 2012)
According to economic theory, regional development can be achieved by economic and non-economic development. By the term regional development we understand an economic and also a social process, which aims to create a viable and productive territory. One of the objectives of regional development is to start the process of building a sustainable competitiveness of the region through the effective use of its potential and spatial peculiarities on the basis of monitoring and analysis of market needs and competitive behavior. Regional development has its own characteristics, which should be respected because they are mainly due to the landscape pattern. Each area fulfills concrete economic and social functions that affect the pattern of the landscape potential. An attractive area has better chance to succeed in the market area, because it attracts financial and high-quality human capital that can provide its further development, prosperity and wealth growth then. The competition of market areas is as strongly as in other markets, so most of the procedure for draft the strategies of the regional development has a common base - searching for competitive advantage. At the present time, in creating competitive advantage, the focus is removing from orientation of the market share growth to the efficiency growth in terms of improving competitive advantage. Every region achieves a competitive advantage in a different way in dependence on its potential, on environment in which exist, on the market in which is active and on its competitors. If the region will be competitive and thrifty, it must capture and retain creative people. This is possible only if combine talent, technology and tolerance in region. Most of new, creative thoughts and ideas originate by interpersonal interaction mainly among different and talented persons. An important role plays an education and contiguous information and knowledge transfer. Talented persons are mostly concentrated in cities, especially in capital cities. In consideration of the population of Slovak Republic is therefore important that all municipalities should have develop their own talents, constrict new talent and practice tolerance by respect for diversity. This approach forms the basis for definition competitive and also creative strategies of development of the municipalities, cities or whole regions. A serious problem that needs to be solving in connection with the development of talents at the local level is the cooperation among government, business sector, universities and cultural institutions. The paper deals with the creativity of regions and its monitoring in the region of Žilina. The measurement will be realized by the selected indicators of creativity.
Keywords: 330